1982
DOI: 10.1111/j.1469-8137.1982.tb03325.x
|View full text |Cite
|
Sign up to set email alerts
|

ECTOMYCORRHIZA FORMATION IN EUCALYPTUS

Abstract: SUMMARYEctomycorrhiza formation by 11, geographically distinct Eucalyptus species and Pinus radiata with 23 diverse ectomycorrhizal fungi was examined in pure culture syntheses. Few differences occurred between the Eucalyptus species in their ability to form ectomycorrhizas with several fungi, thus indicating no evidence for host-fungus specificity within Eucalyptus. Pinus radiata and most Eucalyptus species formed ectomycorrhizas in common with several broad-host-ranging fungi. However, fungus species which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
1

Year Published

1982
1982
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(83 citation statements)
references
References 49 publications
(21 reference statements)
5
77
1
Order By: Relevance
“…comm. ), Eucalyptus spp., in general, can form both AM and ECM associations (Jones, Durall & Tinker, unpublished ;Malajczuk et al, 1981 ;Malajczuk, Molina & Trappe, 1982). In some systems, arbuscular mycorrhizas are the more abundant type initially, with ectomycorrhizas succeeding them over a period of months (Lapeyrie & Chilvers, 1985 ;Chilvers et al, 1987) ; however, the relative abundance of the two types of mycorrhizas can be influenced by the types of host plants previously grown on the site (Oliveira et al 1997).…”
Section: mentioning
confidence: 99%
“…comm. ), Eucalyptus spp., in general, can form both AM and ECM associations (Jones, Durall & Tinker, unpublished ;Malajczuk et al, 1981 ;Malajczuk, Molina & Trappe, 1982). In some systems, arbuscular mycorrhizas are the more abundant type initially, with ectomycorrhizas succeeding them over a period of months (Lapeyrie & Chilvers, 1985 ;Chilvers et al, 1987) ; however, the relative abundance of the two types of mycorrhizas can be influenced by the types of host plants previously grown on the site (Oliveira et al 1997).…”
Section: mentioning
confidence: 99%
“…Early studies by Malajczuk et al (1982) showed few differences in the ectomycorrhiza-forming ability of several eucalypt species from geographically distinct areas with several fungi, including Pisolithus, thus indicating no evidence for Eucalyptus fungus-specificity. However, this observation was not confirmed since Eucalyptus species form little or no association with P. tinctorius strains originally isolated from pine (Burgess et al, 1994;Malajczuk et al, 1990;Oliveira et al, 1994).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover eucalypts do not form ectomycorrhizas with many of the northern hemisphere fungi including Rhizopogon spp. (Malajczuk, Molina and Trappe, 1982).…”
mentioning
confidence: 99%